BLOOD LIPOPROTEINS AS A PLATFORM FOR TRANSPORT OF HYDROPHILIC AND HYDROPHOBIC COMPOUNDS - L. M. Polyakov; R. A. Knyazev; A. V. Ryabchenko; M. V. Kotova; N. V. Trifonova (Сибирский научный медицинский журнал)
The paper discusses the transport functions of the main classes of blood plasma lipoproteins (LP) that are not associated with the metabolism of lipids that make up their composition. The aim of the study was to study the ability of various plasma LP fractions (very low (VLDL), low (LDL) and high density (HDL)) to interact with certain hydrophilic and hydrophobic compounds and show the role of LP as transport forms of xenobiotics in the organs and tissues of the body. Material and methods. The studies were performed with tritium-labeled cytochalasin B, benzylpenicillin, benzanthracene, benzo(a)pyrene, ultracentrifugation of human plasma LP fractions, column chromatography; in vivo experiments with intravenous injection of LP complexes with tritium-labeled benzanthracene were conducted. Results. The ability of various classes of LP to form complexes with hydrophilic (cytochalasin B, benzylpenicillin) and hydrophobic (benzanthracene, benzo(a)pyrene) compounds is shown by the method of ultracentrifugation. More than 50 % of the radioactivity of hydrophilic compounds in human blood plasma was represented in the composition of the LDL and HDL fractions, and in the composition of the VLDL fractions it was minimal – 6.3 and 5.1 %, respectively. A significant part of cytochalasin and benzylpenicillin was also present in the protein infranatant – 43.6 and 40.9 %, respectively. The distribution in blood plasma for hydrophobic (benzanthracene, benzo(a)pyrene) compounds was different. More than 80 % of the radioactivity was represented in the composition of the LP fractions. The polar protein infranatant contained 16.1 % of the radioactivity of benzantracene and 13.6 % of benzo(a)pyrene. The features of the lipophilic xenobiotics uptake by organs and tissues were shown in vivo experiments with intravenous injection of complexes of LP with tritium-labeled benzanthracene to rats. The highest specific radioactivity was found in the liver and adrenal glands after the intravenous injection of 3H-benzanthracene in the composition of VLDL and LDL. Twice less uptake of the labeled drug was observed in the testis and kidneys. Radioactivity decreased in the series: lungs,adipose tissue, thymus, heart, and spleen. A feature of the use of HDL as a platform for 3H-enzanthracene is the intense accumulation of lipophilic xenobiotics in steroid-producing organs: the adrenal glands and testis. Conclusion. The results obtained allow us to consider the real possibility of using blood plasma PL as transport platforms for hydrophilic and hydrophobic compounds into the cells of organs and tissues.